SOX9 as a Predictor for Neurogenesis Potentiality of Amniotic Fluid Stem Cells. (25th August 2014) - Wei, Pei-Cih; Chao, Angel; Peng, Hsiu-Huei; Chao, An-Shine; Chang, Yao-Lung; Chang, Shuenn-Dyh; Wang, Hsin-Shih; Chang, Yu-Jen; Tsai, Ming-Song; Sieber, Martin; Chen, Hua-Chien; Chen, Shu-Jen; et al.
Abstract: Preclinical studies of amniotic fluid-derived cell therapy have been successful in the research of neurodegenerative diseases, peripheral nerve injury, spinal cord injury, and brain ischemia. Transplantation of human amniotic fluid stem cells (AFSCs) into rat brain ventricles has shown improvement in symptoms of Parkinson's disease and also highlighted the minimal immune rejection risk of AFSCs, even between species. Although AFSCs appeared to be a promising resource for cell-based regenerative therapy, AFSCs contain a heterogeneous pool of distinct cell types, rendering each preparation of AFSCs unique. Identification of predictive markers for neuron-prone AFSCs is necessary before such stem cell-based therapeutics can become a reality. In an attempt to identify markers of AFSCs to predict their ability for neurogenesis, we performed a two-phase study. In the discovery phase of 23 AFSCs, we tested ZNF521/Zfp521, OCT6, SOX1, SOX2, SOX3, and SOX9 as predictive markers of AFSCs for neural differentiation. In the validation phase, the efficacy of these predictive markers was tested in independent sets of 18 AFSCs and 14 dental pulp stem cells (DPSCs). We found that high expression of SOX9 in AFSCs is associated with good neurogenetic ability, and these positive correlations were confirmed in independent sets of AFSCs and DPSCs. Furthermore, knockdown of SOX9 in AFSCs inhibited their neuronal differentiation. In conclusion, the discovery of SOX9 as a predictive marker for neuron-prone AFSCs could expedite the selection of useful clones for regenerative medicine, in particular, in neurological diseases and injuries. Abstract : A two-phase study was performed to identify markers of amniotic fluid stem cells (AFSCs) to predict their ability for neurogenesis. High expression of SOX9 in AFSCs was associated with good neurogenesis ability, and these positive correlations were confirmed in independent sets of AFSCs and dental pulp stem cells.